21st century Malaysia islamic values in management and the challenges ahead / Che' Asniza Osman - Osman, Che' Asniza (Universiti Teknologi MARA Cawangan Pahang, 2003)
This article is written to identify the challenges facing by Malaysia through the Islamic administration system practiced today. As enlightened by a minister in the Prime Minister Department, Datuk Seri Dr Rais Yatim by saying, "Malaysia has gone a long way to become an Islamic country" (The Star, October 8,2001) and added, "it had implemented various Islamic elements, such as the Syariah Law, infrastructure and administration". Profoundly, despite the Islamic system used, Malaysia without exception is also facing the drastic economic change, taking place worldly. Malaysia as a model of an Islamic country acknowledges the paradigm change seriously. Her success today is known through out the world but this has actually brought threats to some western countries. Foreseeing the emergence of Islamic countries, several western authors wrote provocatively on Islamic threats. Written by an author from the TIME magazine (15, June, 1992) entitled, The Sword of Islam quoting, "with the death of the Soviet empire some Western policy makers are concerned whether Islamic 'fundamentalism'-may shape up as the next millennial threat to liberal democracy". Could Malaysia be one of them? Management is defined as the process of administering and coordinating resources effectively, efficiently, and in an effort to achieve the goals of the organization (Pamela S.L, Stephen H.G and Patricia M.Fandt, 2004). Thus, the word management is interchangeably used with the word administration in this context.